A 21-bp indel within the LLGL1 gene is significantly associated with litter size in goat. Issue 2 (1st April 2021) - Liu, Nuan; Cui, Wenbo; Chen, Mingyue; Zhang, Xuelian; Song, Xiaoyue; Pan, Chuanying
Abstract: The scribble cell polarity complex component (LLGL1) is part of the cytoskeletal network and is involved in maintaining cell polarity and epithelial integrity. Based on the whole-genome sequencing analysis in goat, LLGL1 gene is suggested as a putative important candidate gene affecting litter size in Shaanbei White Cashmere Goats (SBWC). Therefore, the objective of this study was to uncover the possible novel insertion/deletion (Indel) variant in goat LLGL1 gene and to evaluate its association with litter size of SBWC ( n  = 827). Using the PCR detection and DNA sequencing, the 21-bp indel in the upstream of LLGL1 was firstly founded and two genotypes were identified: II (insertion/insertion) and ID (insertion/deletion), respectively. Association analyses revealed that the 21-bp indel was significantly correlated with litter size ( p  = 0.017). Notably, the individuals with II genotype were significantly greater than that of the genotype ID, and the 'I' allele was dominant. Additionally, the remarkable influence of the indel on traits might be related to the change of DEAF-1-related (NUDR) binding site through bioinformatics analysis. Briefly, the 21-bp indel within the goat LLGL1 gene could be an effective DNA molecular marker and provide valuable theoretical basis for marker-assisted selection (MAS) in goat industry.